Health communication education and training for pharmacy students through role-playing in pharmaceutical service simulations - Muhamad Ramadhan Salam; Muhammad Ramdan Maramis; Wa Ode Marfiah Safitri; Ega Rina; Sulpayanti Djusir; Vista Arianty Wisal; Nur Af’idah Anas; Alfiansyah Weko Ghandigrahita; Lao Ode Muhammad Fahrizal Ahsan (Journal of Community Service and Empowerment, 2025)
Effective communication enhances patient-centered care by improving engagement, outcomes, and health literacy, particularly in chronic disease management. Pharmacists’ communication skills are essential for building trust, improving adherence, and ensuring rational drug use, though gaps remain. Healthcare communication is influenced by psychological, social, and environmental factors, requiring validated and practical training tools. Simulation-based approaches, such as role-playing, effectively strengthen empathy and communication skills in pharmacy students, promoting humanistic care and preparedness to engage diverse patient populations. A community service activity was conducted at SMK Kesehatan Mandonga, Kendari, in April 2025 by STIKES Pelita Ibu, IAI Southeast Sulawesi, and pharmacy students. It involved three stages: preparation, implementation, and evaluation. The event began with a pre-test on healthcare communication, followed by interactive counseling and role-playing exercises to enhance understanding of communication in pharmaceutical practice. Participants’ knowledge increased notably from 77.45% before the intervention to 92.36% afterward, supported by a p-value of 0.001, indicating a significant improvement following the educational and training activities. Role-playing in health communication education is highly relevant for pharmacy students, enabling experiential learning that fosters interpersonal, ethical, and empathetic communication within simulated pharmaceutical care settings.